Contact lenses for continuous corneal temperature monitoring - Moreddu,R; Elsherif,M; Butt,H; Vigolo,D; Yetisen,AK (RSC Advances, 2019)
Temperature variation is a ubiquitous medical sign to monitor ocular conditions including dry eye disease (DED), glaucoma, carotid artery stenosis, diabetic retinopathy, and vascular neuritis. The ability to measure OST in real time is desirable in point-of-care diagnostics. Here, we developed minimally invasive contact lens temperature sensors for continuous monitoring of the corneal temperature. The contact lens sensor consisted of a laser patterned commercial contact lens embedding temperature-sensitive Cholesteric Liquid Crystals (CLCs), which exhibited a fully reversible temperature-dependent color change in the visible spectrum. The contact lens allowed the corneal temperature to be mapped in four key areas, at distances of 0.0, 1.0, 3.0, and 5.0 mm from the pupil's edge. Liquid crystals exhibited a wavelength shift from 738 ± 4 nm to 474 ± 4 nm upon increasing the temperature from 29.0 °C to 40.0 °C, with a time responsivity of 490 ms and a negligible hysteresis. Readouts were performed using a smartphone, which output RGB triplets associated to temperature values. Contact lens sensors based on CLCs were fitted and tested on an ex vivo porcine eye and readouts were compared with infrared thermal measurements, resulting in an average difference of 0.3 °C.